The small big small changes that spark big influence - Martin, Steve J.; Goldstein, Noah J.; Cialdini, Robert B. (Tantor Audio, 2014)
Drawing from extensive research in the new science of persuasion, Steve J. Martin, Noah J. Goldstein and Robert B. Cialdini, prove that small changes can make a big difference.